Genetic comparison among some cultivars of Catharanthus roseus (L.) G. Don. using three intergenic spacers of the chloroplast genome - AGUS HERY SUSANTO; MURNI DWIATI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Susanto AH, Dwiati M. 2024. Genetic comparison among some cultivars of Catharanthus roseus (L.) G. Don. using three intergenic spacers of the chloroplast genome. Biodiversitas 25: 2999-3007. Catharanthus roseus (L.) G. Don belongs to the Apocynaceae family and is recognized as both an ornamental plant and a medicinal herb. By means of both hybridization and mutation breeding, numerous cultivars of C. roseus have been developed over time. This encourages the necessity for molecular characterization to establish a DNA barcode for each cultivar, particularly in relation to its potential as a medicinal herb. Therefore, this study aimed to genetically compare some cultivars of C. roseus based on three Intergenic Spacers (IGS) of the chloroplast genome, namely trnQ-rps16, rps16-trnK, and trnL-rpl32. Ten samples of C. roseus were randomly collected from around Purwokerto City, Central Java, Indonesia, representing cultivars with various corolla and flower eye colors. Universal primers were used to amplify the three molecular markers. The results showed that some insertion-deletions (indels) with rps16-trnK and trnL-rpl32 were observed, indicating some potential barcodes for C. roseus cultivars, following pharmacological analysis. On the other hand, very little genetic difference among samples was found with trnQ-rps16. It can be concluded that some other molecular markers, specifically those more closely related to the expression of flower color in C. roseus, should be explored to obtain candidate DNA barcodes in assisting the authentication of medicinal herbs.